2005
DOI: 10.1038/sj.bmt.1705178
|View full text |Cite
|
Sign up to set email alerts
|

Long-term event-free survivors after high-dose therapy and autologous stem-cell transplantation for low-grade follicular lymphoma

Abstract: Summary:Although follicular lymphoma (FL) is generally responsive to conventional-dose chemotherapy, improved survival in patients with this disease has been difficult to demonstrate. High-dose chemo/radiotherapy followed by autologous stem-cell transplantation (ASCT) can improve response rates, although its effects on survival remain controversial. Between 1990 and 2003, we transplanted 49 patients with low-grade FL at our institution. Twenty-two patients (45%) had undergone histologic transformation at the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Data, mainly from the pre-rituximab era, indicate that the outcome of tFL is improved by HDT-ASCT, i.e. OS increased from approximately 1.5 to 3.5 to 6 years [8][9][10][11][15][16][17][18][19][20][21]. It is however uncertain to what extent this still applies in the rituximab era.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Data, mainly from the pre-rituximab era, indicate that the outcome of tFL is improved by HDT-ASCT, i.e. OS increased from approximately 1.5 to 3.5 to 6 years [8][9][10][11][15][16][17][18][19][20][21]. It is however uncertain to what extent this still applies in the rituximab era.…”
Section: Discussionmentioning
confidence: 91%
“…In the pre-rituximab era, conventional chemotherapy resulted in post-transformation 5-year median overall survival (OS5) below 25 % [8][9][10][12][13][14]. To improve this, high-dose chemotherapy (HDT) with autologous stem cell transplantation (ASCT) was incorporated, leading to OS5 rates around 50 % [11,[15][16][17][18][19][20][21]. As a consequence, HDT-ASCT became a widely accepted treatment strategy in suitable patients with transformed follicular lymphoma (tFL).…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, a biopsy should be performed at the time of post ASCT relapse to establish the subtype of the relapsed lymphoma. High LDH levels and presence of residual disease or chemoresistance at the time of transplantation[120, 122]and advanced age[119, 122] were associated with shorter post ASCT OS and PFS. Comparison of the transplantation outcomes between patients with transformed and non-transformed FL or de novo DLBCL demonstrated no significant differences in OS and PFS in some studies[118, 120], while others suggested inferior outcome for patients with transformed FL [122].…”
Section: Treatment Of Patients With Fl Transformationmentioning
confidence: 99%
“…47,[50][51][52][53] Given the heterogeneity in follow-up, inclusion of various indolent histologies, sample size, and other variables, direct comparison between these studies is problematic. Nearly all included patients were highly selected and young, with a median age in the 40s across most, [51][52][53][54][55] though not all studies, 47,56,57 and only minimal or no disease at time of ASCT. A multicenter Norwegian study of 47 patients is the only prospective series evaluating HDT and ASCT in patients with HT of FL, though conducted in the prerituximab era.…”
Section: Management Challenges Chemotherapy and Transplantationmentioning
confidence: 99%